Development of religious tourism in the tomb perspective intercultural communication - Irwan Syari Tanjung; Hasrudy Tanjung (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The existence of religious tomb tourism has not fully received serious attention from the local government and community, as seen from the lack of tourism facilities and infrastructure such as accommodations, lack of accessibility, lack of promotion, low public awareness of the importance of developing religious tourism, and the lack of professional human resources causing low quality competence. The purpose of this research is to find out how to develop a religious tourism perspective from the perspective of intercultural communication. The research method used is a qualitative method with a descriptive approach. Data collection was carried out by means of observation, interviews, and document research. The results of the study explain that the quality of human resources for the conscious tourism and tomb management groups is still low, not yet professional, or still traditional based on the perceptions of tomb visitors and observers of tourism and culture, but visitor interactions with conscious tourism groups and tomb managers with different cultural identities produce identity relationships that are similar in the sense of forming dynamic social relations between people who both have experience, adequate knowledge, a positive attitude.